PENGEMBANGAN E-BOOK BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS 3 UPT SD NEGERI DOROMUKTI - Fadhila, Salsa Rizki; Agustin, Ina (Universitas Tanjungpura, 2025)
This study was conducted to create a learning tool in the form of an electronic book using Canva to improve the learning achievement of grade 3 students in the field of natural and social sciences (IPAS) at the UPT SD Negeri Doromukti. The background of this study is based on the low learning achievement of students and the minimal use of interactive digital learning media in schools. The ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) is used in research and development (R&D). The data collection process was carried out by means of observation, interviews, expert questionnaires for validation, student and teacher questionnaires for responses, and the implementation of pretest and posttest tests. The validation results prove that the E-book using Canva is declared very qualified by media experts (92.3%), material experts (88.6%), and language experts (93.2%). In practice, this media is also very good with a percentage of responses from teachers reaching 95% and students 91%. The effectiveness of the product can be seen from the better learning outcomes for students with an N-Gain value of 0.56 which is included in the category of quite effective to effective. Ebooks based on Canva have proven to be valid, useful, and efficient in improving students' science learning outcomes.